2021
DOI: 10.4049/jimmunol.2100165
|View full text |Cite
|
Sign up to set email alerts
|

STAT5 Represses a STAT3-Independent Th17-like Program during Th9 Cell Differentiation

Abstract: IL-9–producing Th cells, termed Th9 cells, contribute to immunity against parasites and cancers but have detrimental roles in allergic disease and colitis. Th9 cells differentiate in response to IL-4 and TGF-β, but these signals are insufficient to drive Th9 differentiation in the absence of IL-2. IL-2–induced STAT5 activation is required for chromatin accessibility within Il9 enhancer and promoter regions and directly transactivates the Il9 locus. STAT5 also suppresses gene expression during Th9 cell developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 51 publications
(70 reference statements)
1
11
0
Order By: Relevance
“…IL-2/STAT5 signaling also contributes to Th9 cell differentiation through transcriptional repression where STAT5 represses expression of BCL6 that competes for STAT5 binding at the Il9 locus and limits Th9 differentiation ( 14 , 15 ). Further, we demonstrated that STAT5 suppresses a Th17-like phenotype in differentiating Th9 cells ( 16 ). Despite the importance of IL-2 in the differentiation process, we and others have noted that IL-9-producing Th cells often develop and act to induce protective or auto-immunity in IL-2-limiting environments.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…IL-2/STAT5 signaling also contributes to Th9 cell differentiation through transcriptional repression where STAT5 represses expression of BCL6 that competes for STAT5 binding at the Il9 locus and limits Th9 differentiation ( 14 , 15 ). Further, we demonstrated that STAT5 suppresses a Th17-like phenotype in differentiating Th9 cells ( 16 ). Despite the importance of IL-2 in the differentiation process, we and others have noted that IL-9-producing Th cells often develop and act to induce protective or auto-immunity in IL-2-limiting environments.…”
Section: Introductionmentioning
confidence: 83%
“…The cells were cultured at 37°C for 4 days in plates coated with anti-CD3-(2μg/mL, 2C11, Bio X cell), with soluble aCD28 (4μg/mL, 37.51, Bio X cell), and the Th9-polarizing conditions: anti-IFNγ(10μg/mL), IL-4(20ng/mL), TGFβ(4ng/mL), anti-IL-10R(10μg/mL). IL-2 was neutralized using anti-IL-2 and anti-CD25 antibodies as previously published ( 16 ). In some conditions, we supplemented the cultures with NF-kB activators IL-1β (20ng/mL), IL-33 (20ng/mL), PAM3CSK4 (1μg/mL), DTA1 (5μg/mL) and OX40L (5μg/mL), and we used the NF-kB inhibitors QNZ (2nM, Cayman Chemical) and BAY 11-7082 (0.5μM, Cayman Chemical) with the respective dilution of DMSO as vehicle control.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-2/STAT5 signaling contributed to monitoring the ratio of Th9/Th17-like in vitro and allergic disease. To be specific, STAT5 restricted a Th17-like program in the process of Th9 cell differentiation ( Canaria et al, 2021 ). As shown above, STAT5 regulates the development of inflammation and tumor-related diseases ( Surbek et al, 2021 ).…”
Section: Traditional Chinese Medicines or Herbs Or Natural Compounds ...mentioning
confidence: 99%
“…For example, IL-4-induced pSTAT6 mediates the repression of various genes involved in the alternative macrophage polarization, such as NLRP3 and IL1B , thereby inhibiting inflammasome stimulation and pyroptosis [ 71 ]. Similarly, IL-7-induced pSTAT5 binds to intronic tetrameric STAT sites in B cells to repress the transcription of the IGK gene to suppress immunoglobin gene rearrangement [ 70 ], while IL-2-induced pSTAT5 suppresses a Th17-like program during Th9 cell differentiation [ 83 ].…”
Section: A New Framework To Describe Alternative Stat Functional Modalitiesmentioning
confidence: 99%